Formulation and Activity Test of Clay Mask Stick Preparation with Wheatgrass Extract (Triticum aestivum L.) as an Antioxidant - Maharani, Tri Anita; Budi, Setia; Mustaqimah, Mustaqimah; Noval, Noval (Universitas Ibn Khaldun Bogor, 2025)
Beauty is something that every woman desires. However, many women have problems with their facial skin. One of the causes of skin problems is free radicals. By utilizing plants as the basic ingredients of cosmetic care, namely wheatgrass which is formulated in the form of a clay mask stick preparation that can be effective as an antioxidant. This study aims to determine the effect of variations in the concentration of wheatgrass extract on the physical evaluation of the preparation and to determine the antioxidant activity of the wheatgrass extract clay mask stick preparation. This study is a study with a true experimental posttest-only control design. Formulating wheatgrass extract with different extract concentrations, namely 6%, 8% and 10%, into a clay mask stick preparation. The evaluations carried out were organoleptic tests, homogeneity, pH, spreadability, drying time, irritation and antioxidant activity tests. The results of the study obtained 3 formulations that had good homogeneity, with a safe pH range, spreadability and drying time met the requirements and the preparation did not irritate the skin. Antioxidant activity testing obtained the results of clay mask sticks having antioxidant activity. Formulation 1 has an IC50 value of 29.69 µg/mL, formulation 2 has an IC50 value of 15.28 µg/mL and formulation 3 has an IC50 value of 6.02 µg/mL.